Influence of sex steroid hormones on the adolescent brain and behavior: An update - Vigil, Pilar (Linacre Q, 2016)
This review explains the main effects exerted by sex steroids and other hormones on the adolescent brain. During the transition from puberty to adolescence, these hormones participate in the organizational phenomena that structurally shape some brain circuits. In adulthood, this will propitiate some specific behavior as responses to the hormones now activating those neural circuits. Adolescence is, then, a critical “organizational window” for the brain to develop adequately, since steroid hormones perform important functions at this stage. For this reason, the adolescent years are very important for future behaviors in human beings. Changes that occur or fail to occur during adolescence will determine behaviors for the rest of one's lifetime. Consequently, understanding the link between adolescent behavior and brain development as influenced by sex steroids and other hormones and compounds is very important in order to interpret various psycho-affective pathologies. Lay Summary: The effect of steroid hormones on the development of the adolescent brain, and therefore, on adolescent behavior, is noticeable. This review presents their main activational and organizational effects. During the transition from puberty to adolescence, organizational phenomena triggered by steroids structurally affect the remodeling of brain circuits. Later in adulthood, these changes will be reflected in behavioral responses to such hormones. Adolescence can then be seen as a fundamental “organizational window” during which sex steroids and other hormones and compounds play relevant roles. The understanding of the relationship between adolescent behavior and the way hormones influence brain development help understand some psychological disorders.